A Multiple‐Memory Systems Framework for Examining Attention and Memory Interactions in Infancy. (23rd April 2021) - Amso, Dima; Kirkham, Natasha
Abstract: Visual attention both guides and is guided by learning and memory systems. In this article, we use a multiple‐memory systems framework to examine the interplay between attention and memory that begins in early postnatal life. We review how attention and memory interact to support infant development with respect to perceptual learning about objects and features, item‐in‐context spatial memory, and reinforcement and reward learning. We argue that the multiple‐memory systems approach offers a useful organizational structure for research on interactions between attention and memory.